BARIATRIC SURGERY IMPACT ON GASTROESOPHAGEAL REFLUX AND DENTAL WEAR: A SYSTEMATIC REVIEW - CASTILHO,Ana Virgínia Santana Sampaio (2019)
ABSTRACT Introduction: Several oral problems may be perceived in individuals who were submitted to bariatric surgery, due to metabolic and behavioral changes relative to diet and oral hygiene. Tooth wear appears to suffer impact after bariatric surgery, because there may be an increase in gastroesophageal reflux. Objective: To systematically review the literature regarding the impact of bariatric surgery on gastroesophageal reflux and tooth wear. Method: The following databases were accessed by two independent, calibrated examiners: PubMed, Medline, Lilacs, Scielo and Cochrane using the following descriptors: “bariatric surgery” AND “dental erosion” OR “bariatric surgery” AND “dental erosion” AND “gastroesophageal reflux disease”. After excluding duplicate studies, 12 studies were initially evaluated by the title and abstract. The excluded studies were those without relevance to the present research, literature review studies and case reports. Thus, four articles were included in this study. All the articles evaluated indicated high association between gastroesophageal reflux and tooth wear in patients submitted to bariatric surgery. Association of these outcomes was more evident six months after the surgical procedure. Conclusion: Patients submitted to bariatric surgery showed higher prevalence of gastroesophageal reflux and tooth wear.